The level of urinary endothelin in patients with urinary reflux - Anoush Azarfar; Mohammad Esmaeeli; Mitra Naseri; Shapour Badiee Aval; Fatemeh Ghanee Sharbaf; Sahar Ravanshad; Yalda Ravanshad; Hassan Mehrad-Majd; Sara Molkara (Society of Diabetic Nephropathy Prevention, 2017)
Background: In different tissues, the endothelin is produced by vascular endothelium. They are potent vasoconstrictor peptides. There is a little information about the role of endothelin in reflux nephropathy. Objectives: The aim of this study is to evaluate urinary levels of endothelin in patients with vesicoureteral reflux (VUR). Patients and Methods: It was a cross-sectional study that conducted on 81 children who received voiding cystourethrogram (VCUG). Based on VCUG reports, patients were divided into two groups; with reflux (40 persons) and without reflux (41 persons). We got a urine sample from patients with mid-stream or urine bag method. The endothelin level was assessed with ELISA immunoassay. Data was analyzed using SPSS 16. Results: Based on VCUG reports, 40 patients (49.4%) had urinary reflux, of them 20 cases suffered from unilateral urinary reflux and others from bilateral. Of 40 patients with reflux, 23 cases (57.5% of reflux group) had kidney scar and seven individuals (17.5%) had abnormal kidney sonography. Of patients with urinary reflux, 13 cases (32.5%) had grade1 urinary reflux, 8 cases (20%) grade 2, and 5 cases (12.5%) grade 3 and finally 14 cases (35%) grade 4. The UET-1 levels were significantly higher in VUR patients compared to the control group (P < 0.001). Comparison of mean endothelin levels between two groups was done using Mann-Whitney U test and was statistically significance (P < 0.001). We used Kruskal-Wallis for comparison of endothelin levels in different grades of reflux (P < 0.001). Conclusions: Urine endothelin-1 level can be considered as an alternative to VCUG for screening vesicourethral reflux.